Experimental assessment of the hydro-mechanical behaviour of a shale caprock during CO2 injection. (March 2021) - Minardi, Alberto; Stavropoulou, Eleni; Kim, Taeheon; Ferrari, Alessio; Laloui, Lyesse
Highlights: Short and long-term CO2 injection tests in Opalinus Clay. Different injection methods involve different physical processes; drying vs. imbibition. Water saturation impacts both PE and mechanical response of the material. Mineralogical composition affects the transport properties when injecting CO2 . Abstract: The presented experimental study focuses on the hydro-mechanical characterisation of a shale caprock (Opalinus Clay) in contact with carbon dioxide. The objective of this paper, consists in the evaluation of the material's sealing capacity in terms of entry-pressure, mechanical behaviour and sensitivity of the transport properties to chemo-mechanical effects induced by gaseous and liquid CO2 injection. Two types of Opalinus Clay core samples are tested; shaly and carbonate-rich. The sealing capacity has been evaluated on the shaly OPA according to the stepwise and the residual methods and compared to the results from mercury intrusion porosimetry. The obtained results and the differences associated to the different involved physical processes are discussed and compared with literature data. Injection tests carried out in saturated and unsaturated conditions have revealed that sub-critical CO2 propagation in a water saturated material is not associated with generation of fractures. On the other hand, the generation of capillary forces is affecting the mechanical behaviour beside the sealing capacity. The impact of chemical effects on the permeability of both types of OPA is analysed with long-term CO2 injection tests, where no significant variations of permeability are measured during the exposure time investigated. The challenges related to this type of analysis with laboratory scale experiments are illustrated and new insights on the behaviour of Opalinus Clay when subjected to injection of a non-wetting fluid are highlighted.